Kopeika . The Kopeck - Dykhovichnyj, Ivan (Dykhovichnyj, Ivan, 2002)
Duration: 01:55:00 This movie skims over Russian urban epos of the past 30 years, telling the story of a Soviet automobile, the first VAZ-2101 ever issued, a "people's car" that was in fact a cheap and ugly Fiat knock-off -- and its owners through the time. From a revered status item in the luxury-strapped Soviet reality, to a ridiculed relic from the grim past, through a Politburo member, a physicist, a KGB agent, a prostitute, a gambler, an avant-garde artist, an alcoholic car mechanic, a nouveau riche -- the car suffers through comic and thrilling events of their lives, ruined and restored many a times. There are also several brief appearances of present day Russian cult figures: Sorokin and Dykhovichny both appear in tiny roles; Petlura, a midget from the art posse, pops all over the movie; the "alcoholic pop" singer Sergey Shnurov plays, well, the drunkard who sticks a knife into the fat businessman.